Measuring foreland container port connectivity disaggregated by destination markets: An index for Short Sea Shipping services in Spanish ports. (December 2020) - Martínez-Moya, Julián; Feo-Valero, María
Abstract: The present research aims to develop a Foreland Port Connectivity Index (FPCI) including both qualitative and quantitative variables related to the characteristics of the maritime services provided. To that end, the FPCI incorporates two discount factors—the number of shipping services and destination countries—as penalties to correct for the quality of a port connection. After defining the FPCI, the index is applied to Spanish ports to study their connectivity in terms of container Short Sea Shipping (SSS) services. Although the connectivity of SSS traffic has not been widely studied, it is an interesting case study as small ports play a more relevant role in facilitating access to international markets for importing and exporting companies. According to the results, the port of Valencia is the most connected, followed by the ports of Barcelona and Algeciras. Furthermore, this is the first research paper to attempt to study foreland port connectivity disaggregated by destination market. This geographical approach enables a more precise identification of the main port competitors by destination market, thereby providing more detailed information to support port managers and policy-makers in their decision-making. Highlights: Developing a Foreland Port Connectivity Index based on quantitative and qualitative variables Employ of a market disaggregation approach to explore the liner shipping network An application to SSS container services The index is applied to study the connectivity of the Spanish port system. Shipping patterns have been identified when linking to the Mediterranean area.